Nature tourism planning using river-based resources and recreational assessment for Sungai Dinding, Perak, Malaysia - Nuruddin, Ahmad Ainuddin; Muhammad Ali, Ali (Science Publications, 2013)
Rivers and stream corridors provide a variety of valuable resources including aquatic habitats for fish and other organism, riparian habitats for fish and other organism, riparian habitats for vegetation and terrestrial wildlife. They also provide potential recreational and nature tourism activities. In order to fully identify potential recreational and activities, assessment of recreation resource element should be carried out. The objective of this study was to plan for nature tourism activities using river-based resources and recreational assessment of Sungai Dinding, Manjung, Perak. Uniqueness ratio of each zone for was measured along a 7 km stretch of Sungai Dinding. The highest uniqueness ratio value was Zone 5 with the total value of 13.20. Zone 3 and 1 ranked the second and third respectively with the total value of 9.59 and 8.79. In the physical and chemical category, Zone 5 has the highest score with the value of 6.23. The highest uniqueness value scored in this area is the width of the river during low flow and bank height. Several recreational and nature tourism activities were suggested as a result of the assessment. Building of facilities such as jetties and fishing docks are proposed to enhance recreational experience to the people who want to enjoy the many activities in Sungai Dinding. This approach helps natural resource managers to plan for nature tourism activities.